2011
DOI: 10.5194/nhess-11-1683-2011
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation change in Southern Italy linked to global scale oscillation indexes

Abstract: Abstract. This study investigates precipitation variability in five regions of Southern Italy (Campania, Apulia, Basilicata, Calabria and Sicily) using a homogeneous database of about 70 rain gauges with more than 50 years of observation. First, a statistical analysis was performed through the MannKendall non-parametric test in order to determine rainfall the trend on both yearly and seasonal scales. Then, the relationship between the rainfall and some teleconnection pattern indexes was investigated using Spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 46 publications
5
34
0
1
Order By: Relevance
“…; Caloiero et al . ; Ferrari et al . ) showed the impacts of the North Atlantic Oscillation (NAO) especially in the western Mediterranean area.…”
Section: Discussionmentioning
confidence: 98%
“…; Caloiero et al . ; Ferrari et al . ) showed the impacts of the North Atlantic Oscillation (NAO) especially in the western Mediterranean area.…”
Section: Discussionmentioning
confidence: 98%
“…These trend behaviors in the Euro-Mediterranean area could be related to teleconnection patterns which reflect large-scale changes in the atmospheric wave and influence temperature, rainfall, storm tracks, jet stream location and intensity over vast areas [70,71]. Several past studies [72][73][74] showed the impacts of the North Atlantic Oscillation (NAO) especially in the western Mediterranean area. The influence of the NAO is strongest in winter and early spring.…”
Section: Resultsmentioning
confidence: 99%
“…A strong interdependence among the NAO, precipitation, river discharges and air temperature in some southern Italy regions (Brandimarte et al, 2011;Caloiero et al, 2011) was discovered. Recent studies revealed that the impact of the NAO in Mediterranean areas can also be widely conceived as extendable to snow accumulation, crop production, landslides and soil erosivity (Vicente-Serrano and Trigo, 2011).…”
Section: Introductionmentioning
confidence: 99%